Neuregulin 4 as a novel adipokine in energy metabolism - Liu, Yuanbin; Chen, Mingkai (Frontiers in Physiology, 2023)
Adipose tissue has been shown to play a key role in energy metabolism and it has been shown to regulate metabolic homeostasis through the secretion of adipokines. Neuregulin 4 (Nrg4), a novel adipokine secreted mainly by brown adipose tissue (BAT), has recently been characterized as having an important effect on the regulation of energy homeostasis and glucolipid metabolism. Nrg4 can modulate BAT-related thermogenesis by increasing sympathetic innervation of adipose tissue and therefore has potential metabolic benefits. Nrg4 improves metabolic dysregulation in various metabolic diseases such as insulin resistance, obesity, non-alcoholic fatty liver disease, and diabetes through several mechanisms such as anti-inflammation, autophagy regulation, pro-angiogenesis, and lipid metabolism normalization. However, inconsistent findings are found regarding the effects of Nrg4 on metabolic diseases in clinical settings, and this heterogeneity needs to be further clarified by future studies. The potential metabolic protective effect of Nrg4 suggests that it may be a promising endocrine therapeutic target.